Willingness to participate in future HIV vaccine trials among men who have sex with men and female sex workers living in Nairobi, Kenya - Mutisya, Elizabeth Mueni; Mutua, Gaudensia; Nyasani, Delvin; Nduta, Hannah; Kabuti, Rhoda W.; Muturi-Kioi, Vincent; Omosa-Manyonyi, Gloria; Abaasa, Andrew; Lindan, Krysia; Price, Matt A.; Kimani, Joshua; Anzala, Aggrey Omu (PLOS ONE, 2020)
Objective To evaluate factors associated with willingness to participate in future HIV vaccine trials among men who have sex with men and female sex workers living in Nairobi, Kenya. Background Working with ‘key populations’, those at elevated risk of HIV acquisition, is important to conduct efficient HIV prevention trials. In Nairobi Kenya, HIV infection is higher in men who have sex with men (MSM) and female sex workers (FSW) than in the general adult population, hence the need to establish if they would be willing to participate in future HIV vaccine trials. Methods We administered a structured questionnaire to MSM and FSW enrolled in a simulated vaccine efficacy trial (SiVET). The SiVET was an observational study designed to mimic the rigors of a clinical trial to assess HIV risk characteristics at baseline. After 12–15 months of follow-up, a structured questionnaire was administered to evaluate hypothetical willingness to participate in future HIV vaccine trials. Results Of 250 persons (80% MSM by design) enrolled in SiVET, 214 attended the final study visit and 174 (81%) of them expressed hypothetical willingness to participate in future HIV vaccine trials. These were 82% of MSM and 80% of FSW of those who attended the final study visit. Having a very good experience in the SiVET trial predicted willingness to participate in future HIV vaccine trials. Motivating factors for participation included a desire to receive education about HIV (59%) and to receive healthcare (57%). Conclusions Our data demonstrate high willingness among key populations in Kenya, to participate in future HIV vaccine trials after completing participation in a SiVET. The findings suggest that these groups might be a reliable target population for consideration in future HIV vaccine trials. Assessment of willingness to participate in these populations provides important information that may help to inform future education and recruitment efforts for vaccine trials. Improving the research experience for members of key populations could impact their willingness to participate in HIV vaccine trials.